2015
DOI: 10.1007/s11409-015-9140-8
|View full text |Cite
|
Sign up to set email alerts
|

The instinct fallacy: the metacognition of answering and revising during college exams

Abstract: Students often gauge their performance before and after an exam, usually in the form of rough grade estimates or general feelings. Are these estimates accurate? Should they form the basis for decisions about study time, test-taking strategies, revisions, subject mastery, or even general competence? In two studies, undergraduates took a real multiple-choice exam, described their general beliefs and feelings, tracked their performance for each question, and noted any revisions or possible revisions. Beliefs form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…But clearly this is insufficient, because there is a method to overcome the defeater and the person would be held responsible for their choice whether they overcame the defeater or not. Couchman et al (2016) used a simple method of having examtakers keep track of their level of confidence in each answer, specifically to guard against the transience of memory and several of Tversky and Kahneman's (1974) heuristics. Confidence ratings are a common form of metacognitive assessment, and they found that these in-the-moment self-assessments were predictive of objective accuracy.…”
Section: N O T Ementioning
confidence: 99%
“…But clearly this is insufficient, because there is a method to overcome the defeater and the person would be held responsible for their choice whether they overcame the defeater or not. Couchman et al (2016) used a simple method of having examtakers keep track of their level of confidence in each answer, specifically to guard against the transience of memory and several of Tversky and Kahneman's (1974) heuristics. Confidence ratings are a common form of metacognitive assessment, and they found that these in-the-moment self-assessments were predictive of objective accuracy.…”
Section: N O T Ementioning
confidence: 99%
“…But clearly this is insufficient, because there is a method to overcome the defeater and the person would be held responsible for their choice whether they overcame the defeater or not. Couchman et al (2016) used a simple method of having examtakers keep track of their level of confidence in each answer, specifically to guard against the transience of memory and several of Tversky and Kahneman's (1974) heuristics. Confidence ratings are a common form of metacognitive assessment, and they found that these in-the-moment self-assessments were predictive of objective accuracy.…”
Section: N O T Ementioning
confidence: 99%
“…Although there has been extensive research on monitoring accuracy-that is, how closely judgments about ones' performance are to actual performance (Dunlosky & Metcalfe 2009, Koriat, 1997, 2011, 2012, only a few of these studies examined the accuracy of metacognitive judgments in estimating performance in testing-taking situations, and the reported findings are mixed (e.g., Couchman, Miller, Zmuda, Feather, & Schwartzmeyer, 2016;Nietfeld, Cao, & Osborne, 2005). Furthermore, what is currently known in the literature about monitoring accuracy comes mainly from studies conducted on students from Western countries, where overconfidence bias is relatively common among students and culture is traditionally conceptualized as individualistic (Bol & Hacker, 2012;Dunlosky & Rawson, 2012;Foster, Was, Dunlosky, & Isaacson, 2016;Rawson & Dunlosky, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated monitoring accuracy for local and global metacognitive judgments in a classroom setting (e.g., Couchman et al, 2016;Nietfeld et al, 2005) as well as in the laboratory (e.g., Dunlosky, Rawson, & Middleton, 2005). Local metacognitive judgments are those made for each test item separately, and global metacognitive judgments are an overall estimate of how well one performed on the entire test.…”
Section: Introductionmentioning
confidence: 99%